Disorders of Adipose Tissue and Lipodystrophies: Causes, Consequences, and Treatment Perspectives - Rosińska, Kamila; Janicka, Ewelina Justyna; Skibicka, Julia Natalia; Niedźwiedzka, Monika; Rosiński, Mateusz (Quality in Sport, 2025)
Lipodystrophies are rare metabolic disorders characterized by the loss of adipose tissue, which can manifest as generalized, partial, or localized. This condition is associated with metabolic complications such as insulin resistance, diabetes, hypertriglyceridemia, and liver steatosis. The paper discusses the classification of lipodystrophies by etiology and fat loss extent, including generalized and partial forms, both congenital and acquired. Special focus is placed on HIV-associated lipodystrophy due to the prevalence of antiretroviral therapy. The pathophysiology involves disrupted adipogenesis, leading to abnormal fat distribution and metabolic dysfunction. Diagnosis includes medical history, physical exams, and body composition analysis. Treatment focuses on managing metabolic issues and may involve therapies like metreleptin. OBJECTIVE: This study aims to analyze the pathophysiology, diagnosis, and treatment of lipodystrophies, particularly focusing on congenital, acquired, and HIV-associated forms. It explores the underlying metabolic mechanisms, diagnostic challenges, and current and future therapeutic approaches, including metreleptin and other strategies. MATERIALS AND METHODS: The study relies on scientific research, review articles, and reports on lipodystrophy syndromes, primarily sourced from PubMed, Google Scholar, and Cochrane Library. It examines data related to diagnostics, etiology, and treatment options. CONCLUSIONS: Lipodystrophies are rare and heterogeneous, making diagnosis challenging. Early detection is essential to prevent complications like diabetes and cardiovascular disease. Modern technologies such as dual-energy X-ray absorptiometry (DEXA) help assess body composition more accurately. Although therapies like metreleptin show promise, they remain expensive and difficult to implement. Further research is needed to improve understanding and management of lipodystrophies, and patient education is crucial for better outcomes.